Effects of Combined Versus Singular Verbal or Haptic Feedback on Acquisition, Retention, Difficulty, and Competence Perceptions in Motor Learning. Issue 4 (August 2019) - Frikha, Mohamed; Chaâri, Nesrine; Elghoul, Yousri; Mohamed-Ali, Hasnaa H.; Zinkovsky, Anatoly V.
While augmented feedback (AF) is widely acknowledged to affect motor learning, the effects of mode of feedback on motor learning acquisition, retention, and perceived competence has rarely been studied. The present investigation analyzes the effects of verbal, haptic, and combined (verbal and haptic) feedback when learning a novel gymnastic parallel bars task. Forty-eight physical education students and four expert gymnastics teachers participated in the study. We divided the students into three AF groups (verbal, haptic, and combined) and a no-feedback control group (CG). One gymnastics teacher led the learning sessions, while the others evaluated student performances following familiarization, acquisition, and retention learning phases. All sessions were video recoded, and the experts gave blind assessments according to an adapted gymnastic point code. We recorded task perceived difficulty (PD) and students' perceived self-competency throughout the sessions. A repeated measures analysis of variance revealed a significant effect of AF mode on acquisition and retention such that combined AF was best for learning stability and retention (19.1% improvement for combined vs. 9.9% for haptic and 6.9% for verbal). Similarly, participants in the combined AF group, relative to the verbal and haptic AF groups, also reported lower perceived difficulty and higher perceived self-competency after the retention phase. PE teachers are encouraged to combine verbal and haptic AF when teaching new motor skills.